Regeneration of a recombinant infectious bursal disease virus having four amino acid substitutions in VP2 by reverse genetics - Noor, M; Lüken, C; Das, PM; Islam, MR; Müller, H (Bangladesh Veterinarian, 2015)
Infectious bursal disease virus (IBDV), a virus with a double-stranded, bi-segmented RNA genome, is an economically important pathogen of chickens. Recent understanding of the molecular biology of IBDV has implicated several amino acid residues in the capsid protein VP2 in pathogenicity and tissue culture adaptation. In the present study a recombinant strain of IBDV having four mutations in VP2 (Gln253His, Asp279Asn, Ala284Thr and Ser330Arg) has been generated using reverse genetics. Desired mutations were introduced in the VP2 gene of the cloned cDNA of genome segment A of a very virulent (vv) IBDV by site-directed mutagenesis. Capped RNA transcribed in vitro from cloned cDNA of the modified segment A and wild type segment B was co-transfected into chicken embryo fibroblast (CEF) cell culture. The recombinant virus, designated as BD- 3tcC, was rescued from the transfected cell culture and characterized in vitro. BD-3tcC retained all the four desired mutations and replicated with titres only slightly lower than those of CEF cell-culture-adapted wild-type IBDV. This recombinant strain can be used in future studies for understanding the biological significance of these four amino acid residues in VP2. DOI: http://dx.doi.org/10.3329/bvet.v31i1.22838 Bangl. vet. 2014. Vol. 31, No. 1, 12-19